Data of the crystal structure of xylose isomerase from Streptomyces avermitilisProtein Data BankZENODO - Ki Hyun Nam (Data in Brief)
Xylose isomerase (XI; also known as glucose isomerase) catalyzes the conversion of D-glucose and D-xylose to D-fructose and D-xylulose, respectively. XI is widely used in various industries, such as high-fructose corn syrup and bioethanol production. The discovery and characterization of novel XI variants are important to enhance the effective industrial applications of XI. Recently, the X-ray diffraction data for XI from Streptomyces avermitilis (SavXI) were collected at a synchrotron. The crystal structure of SavXI was determined using the molecular replacement method. The SavXI structure exhibited two unique metal-binding sites at the active site, diverse conformations, and a distinctive conformation of the C-terminal region compared to other XI homologs. This structural information extends the understanding of the molecular properties of the XI family. Here, information on the raw diffraction data images of SavXI, which were not presented in the previous study, is introduced. Detailed data collection and structure determination are reported for future XI structural analyses.